Implementation of The Concept of Niteni, Nirokke, Nambahi In Increasing Sales of Putra Tabah UMKM In Giwangan Main Market, Yogyakarta - Widya Astuti; Engga Tri Cahyono; Clarisa Nindya Franselina; Fariz Najwa Hanan; Nabilla Zhara Anasya; Susana Ema Kelen; Azwar (PT. INOVASI TEKNOLOGI KOMPUTER, 2024)
This study aims to implement the concept of Niteni, Nirokke, Nambahi in an effort to increase sales of UMKM Putra Tabah located in Giwangan Main Market, Yogyakarta. UMKM Putra Tabah is a vegetable trading business that has been operating since 2010 and is now managed by the second generation. Niteni will be implemented by observing the best practices of other successful business actors, in order to understand effective marketing and management strategies. Furthermore, through Nirokke, this UMKM will imitate or adapt digital marketing methods to increase the reach and visibility of its products. Finally, the Nambahi concept will be used to add value to products by introducing new variations and attractive offer packages for customers. Through this study, it is hoped that concrete steps can be identified that can be taken to increase sales and competitiveness of UMKM Putra Tabah. This study not only aims to improve the performance of UMKM Putra Tabah, but also provides a model for other UMKM in facing increasingly competitive market challenges